O conto de fadas na tradição e no contemporâneo: (dois momentos para reflexão) - Fregotte, Ariane (2020)
This research deals with the historical roots of the traditional tales, based on the versions of Cinderella, Perrault (1697) and the brothers Grimm (1812-1815), selected for a comparative analysis with the recreation of Paula Pimenta, in the work Cinderela Pop (2015). Our proposal has a broader objective to identify the variations that the Cinderella tale suffered when placed side by side versions of Perrault and the Brothers Grimm, and Paula Pimenta. Still as an objective, we propose to contextualize the traditional literature, as well as to analyze the differences and similarities between the three selected versions, highlighting the influence of new media in the contemporary version of Paula Pimenta. Therefore, we are guided by the following problematization: is it possible to affirm that the two traditional versions of the short story Cinderella and its recreation in the form of a youth novel in contemporary times are associated with the changes in the written structure of fairy tales that have occurred through the ages? To answer the question, we raised the hypothesis that the reality of oral tradition literature and the emergence of writing helps, in some way, in the understanding, expansion and even densification of the interpretative reading of the tale. The theoretical basis of the work is based on indicators by Italo Calvino (1999), Teresa Colomer (2017), Nelly Novaes Coelho (1991), Bruno Bettelheim (1980), Vladimir Propp (1983), Fernando Segolin (2006), Samira de Mesquita (2006) and Walter Benjamin (2012). Among other considerations, this research points out that the variations since the oral tradition, evidence historical moments that compose a background scenario of the tales transformations, in particular, Cinderella, one of the most outstanding expressions among the children's stories